RGD direct conjugation using co-solvent system to increase cell attachment on poly(lactide-co-glycolide) without change in hydrophilic/hydrophobic property - Lee, Soo-Hong; Chung, Hyung Min; Kim, Young Ha; Kim, Soo-Hyun (ASBM7: ADVANCED BIOMATERIALS VII, 2007)
We have developed a direct conjugation method of RGD (Arg-Gly-Asp) into polylactide (PLA) using co-solvent system, which showed high reaction yield compared to one solvent system presumably due to good solubility of reactants. First, hydroxyl groups a the end of PLA were changed into carboxyl acid by ring opening reaction of succinic anhydride. For a coupling reaction with high solubility, RGD was dissolved in water and then PLA in dioxane Was added into RGD solution in the presence of 1-(3-dimenthylaminopropyl)3-ethylcarbodiimide hydrochloride (EDC). The conjugation of RGD was confirmed by H-1-NMR, GPC and elementary analysis. The RGD conjugated PLA (RGD-PLA) on poly(lactide-co-glycolide) (PLGA) film significantly increased the number of attached cells compared to PLGA without RGD-PLA, while it did not change static contact angle of PLGA. This result demonstrated this conjugation method would be a useful tool to increase cell affinity of biomaterials without change in hydrophilic/hydrophobic property for tissue engineering applications.